Когнітивно-наратологічний аналіз художнього дискурсу (на матеріалі оповідання Г. Джеймса «Поворот гвинта») - Бєляков, Олександр Олександрович; Bieliakov, O. О. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті експлікується методика когнітивно-наратологічного аналізу художнього дискурсу. Матеріалом дослідження послужила новела Г. Джеймса «Поворот гвинта» («The Turn of the Screw»). З огляду на діалогічну модель комунікативної ситуації і когнітивну карту дискурсу (О. О. Селіванова) аналізується взаємодія когні¬тивних і наратологічних характеристик художнього дискурсу. Стратегія дослідження передбачає когнітивно-наратологічний аналіз трьох модулів художньої комунікації: адресанта, тексту та адресата. Research on human intelligence has postulated that studying the structure and use of can provide important insights into the roots of self and the nature of thinking. In that spirit, the article focuses on narrative as a crossroads where cognitology, literary theory and the recent hybrid called «cognitive narratology» (D. Herman) intersect suggesting new directions for understanding and interpreting a literary discourse. The material of the research is «The Turn of the Screw», Henry James’s novella, one of the world’s famous ghost stories. This novella inspired critical debate over the question of “reality of the ghosts and James’s intentions”. The goal of the research is to explain the «narrative-like» nature of “The Turn of the Screw” in terms of the relation between the explicit cues included in a text and the scripts (frames, schemata) on which readers rely in processing those cues. The methodological foundation of the research is made up of the ideas propagated by O.O. Selivanova, G. Cook, P. Stockwell and E. Semino. The main result of the research is demonstrating the interaction between purely narratological phenomena and the methods of cognitive poetic analysis.
The Analysis of Literary Discourse in the Lens of Narrative Theory and Cognitive Science (on the Material of Henry James’s «The Turn of the Screw»)
Keywords: концептуальний простір; conceptual space; модуль адресата; module of the addresser; можливі світи; possible worlds